STRATEGI INTERNALISASI NILAI KARAKTER INTEGRITAS MELALUI PENGAWASAN AKADEMIK DI SMP NEGERI MODEL TERPADU BOJONEGORO - SUSANTO, EDY DWI (Jurnal Penelitian Pendidikan, 2019)
The purpose of this research is to know the strategy of internalizing the character's integrity value through academic supervision and knowing the results of academic supervision to the teacher about the strategy of internalizing the value of character integrity. The method used in this study is School Action Research. The research subjects were 28 teachers of SMP Negeri Model Terpadu Bojonegoro as many as 28 people with details of 7 men and 21 women. Data collection techniques used in this study include documentation, observation, and questionnaire (questionnaire). The results of the research show that the strategy of internalizing the value of character integrity through academic supervision was carried out in two cycles. Each cycle consists of four main stages of activity, namely (a) planning; (b) actions; (c) observation; and (d) reflection. The results of academic supervision show that the teacher has been able to use the internalization strategy of integrity character values through three stages representing the process or stage of internalization, namely the value transformation stage, the transaction transaction stage, and finally the transinternalization stage. There was an increase in the quality of RPP from the first cycle with the average value of 80,68%, up to 98% in the second cycle. In addition, there was also an increase in the quality of learning in the first cycle with an average value of 85.04% to 93.13% in the second cycle. Finally, the level of understanding of teachers about the internalization strategy of the integrity character values of 96.42% chose to be very understanding and understanding.